Role of the interplay between ERK5 and hypoxia in intrahepatic cholangiocarcinoma cells. (March 2023) - Menconi, A.; Gentilini, A.; Lori, G.; Marra, F.; Rovida, E.
Abstract : Background/Aims: Intrahepatic cholangiocarcinoma (iCCA) is an aggressive liver malignancy with limited therapeutic options, and its incidence is increasing in the Western countries. ERK5, a kinase belonging to the mitogen-activated protein kinase family, has been recently shown to be involved in iCCA progression. Hypoxia, a condition that occurs in solid tumors, is involved in malignant transformation mainly activating hypoxia inducible factors (HIF) 1/2 α. This study was undertaken to investigate a possible interaction between hypoxia and ERK5 and to unveil a possible interplay between two potential targets in iCCA. Methods: Two iCCA cell lines (HuCCT-1 and CCLP-1) were used. ERK5, phospho-ERK5, HIF-1α, Glut1 and CAIX were investigated by Western blotting. Gene silencing was performed with shRNA. Pharmacologic inhibitors of ERK5 activity and HIF-1/2 α were used. Quantitative RT-PCR was employed to analyze HIF 1/2 α mRNA expression. MTT and crystal violet assays were used to evaluate cell viability. Results: HIF-1α and HIF-2α mRNA expression was increased in iCCA cells compared to normal human cholangiocytes. HIF-1α protein levels were increased upon hypoxic (0.2% O2 ) conditions with the subsequent upregulated expression of its two targets Glut1 and CAIX. An increase of ERK5 phosphorylation was observed upon hypoxia, while in ERK5-depleted cells an enhancement of total and nuclear HIF-1α was found, indicating an interplay among the two signaling pathways. Combined treatment with HIF and ERK5 inhibitors synergized to reduce cell viability compared to single treatments. Among the different HIF and ERK5 inhibitors used, KC7F2 and JWG071 resulted the more efficient combination. Conclusions: ERK5 is activated upon hypoxic conditions and cross-talks with HIF in CCA cells.